Deliberation as a Means of Preventing a Disfunctional Impact of Conflicts - Krzewińska, Aneta; Wiśniak, Marzena (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The article concerns a conflict in an organization, however, it does not treat a conflict as a dysfunctional element to the activity of that organization, but as an inevitable and often beneficial phenomenon – as long as it is properly managed. The authors focus on factors, which change a potentially beneficial phenomenon into a dysfunctional one: on conditions favouring conflict formation, improper internal communication, destructive behaviour of conflict sides with a particular regard to managers. In all their considerations the authors enumerate benefits of conflicts with a positive influence of deliberation procedures, describing their own research experiences related to organizing such a deliberative discussion in a cultural institution (Philharmonic).